UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR KIMIA MELALUI PENDEKATAN PEMBELAJARAN KOOPERATIF DENGAN METODE JIGSAW BAGI KELAS X-1 SEMESTER GENAP TAHUN 2008/2009 - Sunardi, Sunardi (Sainteks, 2011)
The purpose of this research was to increase activity and learning results of students in chemistry by cooperative learning method JIGSAW type. Subject of this research is student class X-1 the Hight Middle School (SMA) Country 1 Banjarnegara. On chemistry, especially recitative matter, is founded phenomenon of it decrease student activity which is remarked by a few question from student, low of student learning result on the everage 65, the mastery leraning is 60 %, and low of cooperation capability. This case ensued learning in the class is dominated by teacher. Action of the research is executed with two cycles. There is four phase In every cycle, i.e.: planning, acting, observing, and reflecting. Data analysis have used technic of descriptive-comparative analysis, by comparing test value at early condition, first cycle and twice cycle, and descriptive-qualitative analysis building on observation result and reflecton from every cycle. The result of this research shows there is increasing of student learning activity, cycle by cycle. The first cycle is 60 %, and then cycle is 90 %. So, individual learning achievement increased at first cycle 69,06 % and twice cycle 77, 81 %, and then mastery learning of student also raised, the first cycle is 37,5 % and the twice is 75 %.Keywords: cooperative learning JIGSAW type, learning achievement, and hemistry.